PENGARUH CURRENT RATIO, DEBT EQUITY RATIO, DEVIDEND PAYOUT RATIO, UKURAN PERUSAHAAN, PRICE BOOK VALUE, EARNING PER SHARE, RETURN ON ASSET, DAN OPERATING PROFIT TERHADAP PRICE EARNING RATIO (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI tahun 2013 – 2016) - Edi Susanto; Marhamah Marhamah (JAB (Jurnal Akuntansi & Bisnis), 2018)
Price Earning Ratio reflects the relationship between the market price of the common stock (common stock) and earnings per share. Price Earning Ratio is seen by investors as a measure of the strength of the company to earn profits in the future. Companies that have a great opportunity to grow normally have a high price earning ratio. Conversely, a low price earning ratio for the company at risk.This study aims to empirically examine the influence of the Current Ratio, Debt Equity ratio, dividend payout ratio, Company Size, Price Book Value, Earnings Per Share, Return on Assets, and Operating Profit on Price Earning Ratio in Manufacturing companies listed in Indonesia Stock Exchange in 2013 - 2016 population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange (IDX) in 2013 - 2016 samples were selected using purposive sampling method in order to obtain a total of 18 issuers.The results of this study indicate that the Debt Equity Ratio, dividend payout ratio, Price Book Value, Return on Assets, Operating profit significantly influence the price earning ratio. While the current ratio, Company Size, Earnings Per Share has no significant effect on the price earning ratio. Coefficient of determination (Adjusted R Square) of 0.915. This means that the variable Current Ratio, Debt Equity ratio, dividend payout ratio, Company Size, Price Book Value, Earnings Per Share, Return on Assets, and Operating Profit 91.5% have a role together in order to explain or describe variables Price Earning Ratio. Keyword:                    Current Ratio, Debt Equity ratio, dividend payout ratio, Company Size, Price-book value, Earning Per Share, Return on Assets, operating profit, and Price earning Ratio